New sensor based on membranes with magnetic nano-inclusions for early diagnosis in periodontal disease - Totu, Eugenia Eftimie; Isildak, Ibrahim; Nechifor, Aurelia Cristina; Cristache, Corina Marilena; Enachescu, Marius (ELSEVIER ADVANCED TECHNOLOGY, 2018)
A series of sodium selective membranes with magnetic nano-inclusions using p-tertbutyl calix[4]arene as ionophore and polymeric matrix (polyvinyl chloride) have been developed, and the corresponding sodium selective sensors were obtained for the first time. A linear range was registered between 3.1 x 10(-5) and 10(-1) mol dm(-3) and near Nemstian electrochemical answer: 55.73 mV/decade has been recoreded for PVC (polyvinyl chloride) - based sodium selective sensor, with a response time of 45 s. Due to their small dimensions, sensors could be used for measuring ions from the gingival crevicular fluid directly into the peri-odontal pocket, avoiding the difficulties of collecting an appropriate amount of fluid for analysis. Alterations in the inorganic ions level could be evidenced with this new device, assisting the early diagnosis and prevention of periodontal disease.
Keywords: Magnetic nano-carriers; Polymeric ion-selective electrodes; Needle sodium sensor; Ion-selective polymeric matrix; Periodontal pocket; ION-SELECTIVE ELECTRODES; GINGIVAL CREVICULAR FLUID; CIRCADIAN-RHYTHMS; SODIUM; NANOPARTICLES; DEFINITIONS; TETRAESTER; POTASSIUM; BEHAVIOR; CALCIUM; Biophysics; Biotechnology & Applied Microbiology; Chemistry; Electrochemistry; Science & Technology - Other Topics